Studi Perbandingan Perilaku Struktur Shear Wall dan Base Isolation Type Lead Rubber Bearing pada Rumah Sakit di Surabaya - Permana, Dimas; Sutriono, Bantot; Rochmah, Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Surabaya is an earthquake-prone area due to its location on an active fault zone, namely the Kendeng Fault Zone. Hospitals play a crucial role during disasters; therefore, a strong structure is required to withstand various loads, including seismic loads. This study aims to compare the structural behavior of a hospital building using shear walls and a base isolation system with Lead Rubber Bearings (LRB). The comparison was carried out through modeling of both the existing structure and the modified structure using ETABS v.22 software. The results show that the structure with base isolation has smaller inter-story drifts and P-Delta effects, especially on the upper floors. The base isolation system is also more effective in damping seismic forces, maintaining structural stability, and enhancing building safety. Based on the analysis, the LRB base isolation system proves to deliver better structural performance compared to the shear wall system in resisting earthquake loads.